Presence of clonal T cell populations in chronic B lymphocytic leukemia and smoldering myeloma. - Tao Wen; Håkan Mellstedt; Mikael Jondal (1990)
Clonality in the non-neoplastic T cell population was investigated in 21 patients with B cell chronic leukemic (B-CLL) or multiple myeloma (MM) by probing for TCR beta chain gene rearrangements using Southern blot analysis. In three patients with a benign form of B-CLL (stage 0), and in one patient with smoldering MM, evidence was found for predominant T cell clones. As cellular immunity against the malignant cells may be important in leukemia, the results are discussed in view of the potential role of T cell immunity in B-CLL and MM.